Cognitive disturbance among elderly Taiwanese patients after elective surgery - Lou, Meei-Fang (My University, 2001)
Acute confusion or delirium is an indicator of cognitive disturbance and is a significant health problem for the hospitalized elderly. The purposes of the study were: (1) To test a theoretical model about post-surgical cognitive disturbance; (2) To identify the most efficient items from the MMSE for assessment of cognitive function; and (3) To describe variations of cognitive/behavioral changes during the course of delirium. Data for this study came from a prospective cohort study entitled "Confusion in the hospitalized elderly patient" (Dai, Lou, & Yip, 1996). The data were collected in a medical center in Taiwan from 1995 to 1997. For the first purpose, the findings showed that cognitive function (beta = .50, p < .001), physical function (beta = -.34, p < .001), and physiological stability (beta = -.21, p < .01) had direct effects on post-surgical cognitive disturbance. Physical function and cognitive function also affected post-surgical cognitive disturbance indirectly through physiological stability. These variables accounted for 67% of the total variance of post-surgical cognitive disturbance.Using item response analysis, the original 30-item MMSE was reduced to 16 items. For the 16-item MMSE, four factors were extracted. These 16 items were related to orientation to time, orientation to place, language, attention and calculation, recall and visual construction. The proposed new cutoff point for the 16-item MMSE was 11. This new cutoff point was determined for the purpose of over-identifying patients at risk in order to ensure early detection and prevention from the onset of cognitive disturbance.The findings for the third purpose of the study showed that surgery was a stressful event to the elderly, especially for those less cognitively intact. Subjects who experienced delirium had significantly lower scores on the MMSE and all other measures than the non-delirious subjects at every stage of hospitalization. The major changes in behavior were noted in orientation, registration, and recall abilities.The findings from this study suggest that mental status and physical functioning assessments on admission are necessary to identify patients at risk for post-surgical cognitive disturbance. These findings can be incorporated into routine nursing care that will increase the efficiency of nursing.
Thesis (Ph. D.)--University of Washington, 2001
Keywords: Theses--Nursing